IMPLEMENTASI EXPERIENTIAL MARKETING DALAM KOMUNIKASI PEMASARAN THE HALLWAY KOSAMBI BANDUNG - Nisa Lathifah (Universitas Informatika dan Bisnis Indonesia, 2021)
This research is titled experiential marketing implementation in marketing communication Of The Hallway Kosambi Bandung. The purpose of this study is to find out the application of elements of Experiential Marketing Modules (SEMs), such as sense, feel, think, act and relate. As well as to find out the visitor experience of experiential marketing strategies in marketing communications The Hallway Kosambi Bandung. This research uses qualitative methods with a case study approach. The data collection techniques in this study are interviews, observations and documentation. The result of this research is the application of five modules of Experiential Marketing Strategies (SEMs), namely sense of sight (sight) and smell (scent), feel at the feeling of joy with the existence of various facilities that make visitors comfort, think on exciting young events, creative and allow social interaction, act on the concept of The Hallway hallway hallway which is current with many interesting spots for photos and relate marketing to the concept of The Hallway as a space. Creative collaborative young people in kosambi traditional market and experiential marketing that is felt is the experience of young people